Chlamydia trachomatis Plasmid Gene Protein 3 Is Essential for the Establishment of Persistent Infection and Associated Immunopathology - Yang, Chunfu (mBio, 2020)
Chlamydia trachomatis is an obligate intracellular bacterial pathogen that causes blinding trachoma and sexually transmitted disease afflicting hundreds of millions of people globally. A fundamental but poorly understood pathophysiological characteristic of chlamydial infection is the propensity to cause persistent infection that drives damaging inflammatory disease. The chlamydial plasmid is a virulence factor, but its role in the pathogenesis of persistent infection capable of driving immunopathology is unknown. Here, we show by using mouse and nonhuman primate infection models that the secreted plasmid gene protein 3 (Pgp3) is essential for establishing persistent infection. Ppg3-dependent persistent genital tract infection resulted in a severe endometritis caused by an intense infiltration of endometrial submucosal macrophages. Pgp3 released from the cytosol of lysed infected oviduct epithelial cells, not organism outer membrane-associated Pgp3, inhibited the chlamydial killing activity of antimicrobial peptides. Genetic Pgp3 rescue experiments in cathelin-related antimicrobial peptide (CRAMP)-deficient mice showed Pgp3-targeted antimicrobial peptides to subvert innate immunity as a pathogenic strategy to establish persistent infection. These findings provide important advances in understanding the role of Pgp3 in the pathogenesis of persistent chlamydial infection and associated immunopathology.